2019
DOI: 10.18549/pharmpract.2019.1.1304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of renal drug dosing adjustment in chronic kidney disease patients at two university hospitals in Lebanon

Abstract: Background: Inappropriate medication dosing in patients with chronic kidney disease can cause toxicity or ineffective therapy. Patients are at a high risk of developing related adverse events caused by the altered effect of drugs in conjunction with the use of polypharmacy to treat comorbid conditions. This necessitates adequate renal dosing adjustments. Objective: The current study aims at assessing whether appropriate dosing adjustments were made in hospitalized patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
49
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 22 publications
3
49
3
2
Order By: Relevance
“…Previous studies in patients with advanced CKD have shown contrasting results. Some studies have reported that in patients with advanced CKD the likelihood of PIP is less due to more vigilant monitoring and nephrology consultations, while other studies have shown an increased number of problems [24][25][26]. Further research to understand the phenomenon of PIP in general practice is needed, possibly leading to the design of interventions to optimise medication prescribing in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in patients with advanced CKD have shown contrasting results. Some studies have reported that in patients with advanced CKD the likelihood of PIP is less due to more vigilant monitoring and nephrology consultations, while other studies have shown an increased number of problems [24][25][26]. Further research to understand the phenomenon of PIP in general practice is needed, possibly leading to the design of interventions to optimise medication prescribing in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The study also revealed that 16.11% of beta-blockers contain underdose,14.09% of short duration, 32.89% of overdose, 39.60% of long duration, 35.57% of incorrect frequency, and 53.02% of incorrect route of administration, but this result was higher when compared with the research done on the USA due to the lack of updated information in [34]. Similar findings were reported in Lebanon in which beta-blockers were the most commonly prescribed class of medication requiring dosage adjustment [35]. The problem of under dose and short duration leads to the reduction of the effectiveness of treatment which leads to treatment failure and different complications.…”
Section: Discussionmentioning
confidence: 64%
“…CKD patients are the high-risk population for drug related problems, and among them, medication dosing errors are the most prevalent in these patients. 7,27,28 A large number of published studies 7,15,19,[27][28][29][30][31][32][33][34] have determined the medication dosing error in these patients, but unfortunately, few to none published studies were, to our knowledge, conducted in this part of the region.…”
Section: Discussionmentioning
confidence: 99%